Seasoning Sauce Production from Vegetable Paste - Chompoo, Mayuree; Damrongwattanakool, Nanthina (Journal of Food Technology, Siam University, 2021)
Vegetable paste is the local food product of Chae Hom District, Lampang Province which was made of mustard green. It is widely used in the Upper Northern region due to its taste and high nutrition. This study aims to use the vegetable paste to be made into seasoning sauce in order to increase the value of the local product. Diluting the vegetable paste with water at ratio 60:40 (vegetable paste: water) and developing the recipe using the mixture design experiment. The results showed that the selected recipe with the highest sensory evaluation scores consisted of 65 wt% diluted vegetable paste liquid, 5 wt% corn flour, 30 wt% cane sugar, 4 wt% salt and 8 wt% pepper. The optimal thermal process condition was at 93.3ºC for 20 minutes. The proximate analysis of sauce showed 3.66 % protein, 15.04 %fat, 13.20 %ash, 3.32 %fiber, 24.46 % carbohydrate content and 14 free amino acids analyzed by High Performance Liquid Chromatography (HPLC) was detected in this developed sauce. Physical and microbiological properties were also determined, acidity and pH were 0.74% and 3.35, respectively. Microorganisms analyzed by total plate count method were 3.0x102 CFU/g. Coliform bacteria, Yeast and mold were not detected. The result complied with the microbiological criterion standard for sauce established by TISI. 1317-2538.